Matters of Care in Alberta’s “Inspiring Education” Policy: A Critical Feminist Discourse Analysis - Bohachyk, Laura (Alberta Journal of Educational Research, 2017)
Using the ethics of care as a theoretical lens, alongside the techniques of discourse analysis, I critically analyze texts from Alberta’s Inspiring Education policies. On the basis of this analysis, I identify two discourses: the sentimental treatment of care and the “facilitator discourse.” I argue that a caring teacher-student relationship is more complex than a doting teacher responding to the desires of a “learner.” We must begin to reflect in educational policies the reciprocity of caring educational relationships, the rightness of mutually accepted authority, and the skills required to competently perform the work of caring. Adoptant la perspective théorique de l’éthique des soins et m’appuyant sur les techniques de l’analyse du discours, je fais une analyse critique de textes tirés des politiques albertaines sur l’inspiration et l’éducation. À partir de l’analyse, j’identifie deux discours : la perspective sentimentale des soins et le discours « facilitateur ». Je maintiens qu’un rapport chaleureux entre un enseignant et un élève est plus complexe que les actions d’un enseignant adorant qui répond aux désirs d’un « apprenant ». Nos politiques en matière d’éducation doivent commencer à refléter la réciprocité des rapports éducatifs chaleureux, la justesse d’une autorité mutuellement acceptée et les habiletés nécessaires pour bien accomplir le travail en soins dans un milieu scolaire.